Renin Angiotensin System Inhibitors Reduce Aortic Stiffness and Flow Reversal After a Cryptogenic Stroke. Issue 1 (7th August 2020) - Soulat, Gilles; Jarvis, Kelly; Pathrose, Ashitha; Vali, Alireza; Scott, Michael; Syed, Amer A.; Kinno, Menhel; Prabhakaran, Shyam; Collins, Jeremy D.; Markl, Michael
Abstract : Background: Blood flow reversal is a possible mechanism for retrograde embolism in the setting of high‐risk atherosclerotic plaques in the descending aorta (DAo). Evidence suggests that pulse wave velocity (PWV) is a determinant of blood flow reversal and can be reduced by the destiffening effect of renin‐angiotensin system inhibitors (RASI). Purpose: To evaluate the impact of antihypertensive therapy on in vivo changes in PWV and flow reversal in patients with cryptogenic stroke. Study Type: Prospective. Population: Sixteen patients (69 ± 9 years; 10 males) included after cryptogenic stroke. Field Strength/Sequence: 3T. 4D flow sequence (temporal resolution = 19.6 msec) Assessment: Patients underwent aortic MRI at baseline and at 6‐month follow‐up. Patients received standard‐of‐care antihypertensive therapy that were classified as RASI vs. non‐RASI medications (ie, destiffening vs. nondestiffening).We compared aortic PWV, flow reversal fraction (FRF), aortic measurements, cardiac function, and other aortic and cardiac measurements in the antihypertensive therapy groups. Statistical Tests: Two‐tailed paired or unpaired Student's t ‐tests (normal distributions) or Wilcoxon tests (nonnormal distribution). Univariate correlations using Pearson correlation coefficients. Results: There was a significant decrease in PWV in the RASI ( n = 10) group (9.4 ± 1.6 m/s vs. 8.3 ± 1.9 m/s; P  < 0.05), as well as FRF (18.6% ± 4.1% vs. 16.3% ± 4.0%; P  < 0.05) between baseline and the 6‐month MRI studies. There were no changes in PWV or FRF in the non‐RASI ( n = 6) group ( P = 0.146 and P = 0.32). A decrease in FRF was significantly correlated with a decrease in PWV ( r = 0.53; P  < 0.05). Data Conclusion: The findings of our study suggest that RASI therapy after cryptogenic stroke resulted in a decrease of blood flow reversal and aortic stiffness. Evidence Level: 1 Technical Efficacy Stage: 4